Optogenetic Delineation of Receptor Tyrosine Kinase Subcircuits in PC12 Cell Differentiation. Issue 3 (21st March 2019) - Khamo, John S.; Krishnamurthy, Vishnu V.; Chen, Qixin; Diao, Jiajie; Zhang, Kai
Summary: Nerve growth factor elicits signaling outcomes by interacting with both its high-affinity receptor, TrkA, and its low-affinity receptor, p75NTR. Although these two receptors can regulate distinct cellular outcomes, they both activate the extracellular-signal-regulated kinase pathway upon nerve growth factor stimulation. To delineate TrkA subcircuits in PC12 cell differentiation, we developed an optogenetic system whereby light was used to specifically activate TrkA signaling in the absence of nerve growth factor. By using tyrosine mutants of the optogenetic TrkA in combination with pathway-specific pharmacological inhibition, we find that Y490 and Y785 each contributes to PC12 cell differentiation through the extracellular-signal-regulated kinase pathway in an additive manner. Optogenetic activation of TrkA eliminates the confounding effect of p75NTR and other potential off-target effects of the ligand. This approach can be generalized for the mechanistic study of other receptor-mediated signaling pathways. Graphical Abstract: Highlights: Non-neuronal optogenetics allows for the control of receptor tyrosine kinase activity Tyrosine 490 of TrkA directly activates the ERK signaling pathway Tyrosine 785 of TrkA activates ERK signaling through the PLCγ-PKC pathway Tyrosines 490 and 785 of TrkA both contribute to PC12 cell differentiation Abstract : Khamo et al. developed a non-neuronal optogenetic system to activate TrkA signaling using blue light. In combination with pharmacological inhibition, the authors delineate the signaling role of key physiological tyrosines in the TrkA intracellular domain. Tyrosines 490 and 785 both induce PC12 cell differentiation through the ERK signaling pathway.